Using yeast-based probiotic as dietary supplement during transition period to improve performance of dairy cows - Niknia, AD; Vakili, R; Mokhtarpour, A; Palangi, V (Journal of the Hellenic Veterinary Medical Society, 2025)
A study was conducted to investigate the effect of dietary probiotic supplementation on dairy cow dry matter intake (DMI), milk production, milk composition and somatic cell count (SCC), rumen pH, and serum parameters (glucose, urea, alanine aminotransferase; ALT and aspartate aminotransferase; AST) during transition. Totally 24 multiparous dairy cows were randomly assigned to 3 groups (eight cows/group) fed the same diets supplemented without probiotics (Control group) and with probiotics at the rate of 15 or 30 g live yeast culture/cow daily (Treated groups) for 5 weeks (transition period; from 2 weeks’ pre-partum to 3 weeks post-partum). DMI and milk yield were recorded daily and the milk composition, SCC, rumen pH, and serum parameters were measured every week. A higher DMI and greater average daily milk yield were found in Saccharomyces cerevisiae treated groups as compared to the control groups (P<0.05). There was no significant difference in rumen pH between the control and 15g yeast-supplemented groups, but the higher dose of yeast increased (P<0.05) rumen pH. In probiotic-fed cows, milk fat was increased (P<0.05) and somatic cell count decreased (P<0.05), while milk protein and SNF were unchanged. When yeast was included in the diet, the serum concentration of glucose and urea in cows increased (P<0.05) compared with those of control. However, the other two serum parameters remained consistent across groups. It was concluded that the inclusion of yeast Saccharomyces cerevisiae into the diet of dairy cows during the transition period improved performance regarding enhanced milk yield and enhanced milk quality. Data showed the identical (P>0.05) effect of both yeast levels on dairy cows' performance, which suggests the use of a lower level (15 g) in practice.